Leadership Contestation and Foreign Policy Fragmentation among Muslim States on the Palestinian Issue - Syafiuddin Fadlillah (Dauliyah Journal of Islamic and International Affairs, 2026)
The Palestinian issue has long been regarded as a symbol of normative solidarity and the collective commitment of the Muslim world to global justice. However, in practice, the foreign policy responses of Muslim-majority states toward Palestine demonstrate significant variation. This article aims to analyze the fragmentation of these responses and to explain the political factors shaping such differences within the broader dynamics of leadership in the Muslim world. This study employs a qualitative comparative approach using structured focused comparison and process tracing to examine representative cases reflecting four major response patterns: resistive–confrontational (Iran and Turkey), diplomatic–multilateral (Indonesia, Malaysia, and Qatar), pragmatic–normalization (the United Arab Emirates, Bahrain, and Morocco), and minimal or low-profile (Oman). The findings reveal that fragmentation is not merely a reflection of differing attitudes toward Palestine, but is closely linked to domestic legitimacy strategies, regime stability considerations, and states’ positions within regional and global political structures. The Palestinian issue functions as a strategic reference in foreign policy formulation, where Muslim states calibrate normative commitments with national interests and international alliances. This study contributes to international relations literature by offering an empirical analytical framework to understand the variation of Muslim states’ responses, demonstrating that religious solidarity does not automatically translate into a unified foreign policy.